The Effect of Candesartan Alone and Its Combination With Estrogen on Post-traumatic Brain Injury Outcomes in Female Rats - Hajmohammadi, Mojdeh; Khaksari, Mohammad; Soltani, Zahra; Shahrokhi, Nader; Najafipour, Hamid; Abbasi, Reza (Frontiers in Neuroscience, 2019)
Aim: The aim of this study was to evaluate the effect of candesartan (angiotensin II type I receptor blocker) alone and its combination with estrogen on the changes in brain edema, intracranial pressure (ICP), and cerebral perfusion pressure (CPP) following diffuse traumatic brain injury (TBI) in female rats. Methods: TBI was induced in ovariectomized female rats using Marmarou's method. The treatment groups received low-dose (LC) and high-dose (HC) candesartan, estrogen (E2), a combination of estrogen vehicle and candesartan vehicle (oil + vehicle), or a combination of estrogen with low-dose (E2 + LC), or with high-dose (E2 + HC) candesartan. ICP and CPP were measured before and several times after TBI, and the brain water content (brain edema) was measured 24 h after TBI. Results: After the TBI, brain edema and ICP in the estrogen group were lower than in the vehicle and TBI groups. Brain edema and ICP in the HC group were lower than in the vehicle group after TBI. Although there was no significant difference in brain edema and ICP between the LC and vehicle groups, significant differences in these variables were observed when the E2 + LC and E2 + HC groups were compared with the oil + vehicle group after TBI. A significant increase in CPP was observed in the estrogen group 4 and 24 h post-TBI, while this increase was found in the HC and E2 + LC groups 24 h post-TBI. Conclusions: A low dose of candesartan did not exert a protective effect on TBI outcomes, but such an effect did appear after combination with estrogen. This finding suggests that interaction between low-dose candesartan and estrogen improves TBI-induced consequences.